2006
DOI: 10.2134/jeq2006.0157
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Watershed‐Scale Land Use Change on Stream Nitrate Concentrations

Abstract: The Walnut Creek Watershed Monitoring Project was conducted from 1995 through 2005 to evaluate the response of stream nitrate concentrations to changing land use patterns in paired 5000-ha Iowa watersheds. A large portion of the Walnut Creek watershed is being converted from row crop agriculture to native prairie and savanna by the U.S. Fish and Wildlife Service at the Neal Smith National Wildlife Refuge (NSNWR). Before restoration, land use in both Walnut Creek (treatment) and Squaw Creek (control) watersheds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 43 publications
5
87
3
Order By: Relevance
“…2) were indicative of degraded stream conditions throughout the study watershed. Nitrate concentrations at study sites generally exceeded summer values recently reported from streams in other row-crop dominated watersheds of the Midwestern U.S.A., where nitrate concentrations are consistently among the highest in the nation (Bernot et al, 2006;Figueroa-Nieves et al, 2006;Schilling and Spooner, 2006;Heatherly et al, 2007;Renwick et al, 2008;Wagner et al, 2008;Diebel and Vander Zanden, 2009;Warrner et al, 2009). Additionally, nitrate concentration at each of our study sites (range 5 5.6-29.0 mg/L) was higher than 3.2 mg/L, a threshold value that, based on a USEPA Wadeable Streams Assessment, is indicative of poor conditions in Midwestern streams (Van Sickle and Paulsen, 2008).…”
Section: Results Land Cover Stream Habitat and Invertebrate Assemblagescontrasting
confidence: 56%
See 1 more Smart Citation
“…2) were indicative of degraded stream conditions throughout the study watershed. Nitrate concentrations at study sites generally exceeded summer values recently reported from streams in other row-crop dominated watersheds of the Midwestern U.S.A., where nitrate concentrations are consistently among the highest in the nation (Bernot et al, 2006;Figueroa-Nieves et al, 2006;Schilling and Spooner, 2006;Heatherly et al, 2007;Renwick et al, 2008;Wagner et al, 2008;Diebel and Vander Zanden, 2009;Warrner et al, 2009). Additionally, nitrate concentration at each of our study sites (range 5 5.6-29.0 mg/L) was higher than 3.2 mg/L, a threshold value that, based on a USEPA Wadeable Streams Assessment, is indicative of poor conditions in Midwestern streams (Van Sickle and Paulsen, 2008).…”
Section: Results Land Cover Stream Habitat and Invertebrate Assemblagescontrasting
confidence: 56%
“…Although constituting a comparatively small percentage of area, urban land cover has increased as the number of people residing in Iowa's urban centers has increased (e.g., from 1.26 million in 1950 to 1.71 million in 2009; IDNR, 2000;USCB, 2010). Due to intensive land use and associated contaminant inputs to aquatic ecosystems, 77% of monitored Iowa river and stream segments and 69% of Iowa lakes are classified as ''impaired'' or ''potentially impaired,'' and pollutant loads from Iowa contribute to hypoxia in the Gulf of Mexico (Schilling and Spooner, 2006;IDNR, 2010). With urban expansion and greater economic incentives to intensify agricultural production, threats to aquatic ecosystem condition in Iowa are expected to increase (Secchi et al, 2008;Rayburn and Schulte, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We argue that summer riparian NO 2 3 production is enhanced by subdaily variations in surficial soil oxygen caused both by precipitation events and by soil evaporation and transpiration. These events induce diurnal fluctuations in groundwater tables during the summer, which can be several centimeters during the growing season (Figure 8) as has been seen elsewhere [Loheide et al, 2005;Schilling and Spooner, 2006;Flewelling et al, 2011]. A second source region of NO 2 3 is deeper riparian hollow soils (on the order of 10-50 cm).…”
Section: 1002/2015wr016937mentioning
confidence: 66%
“…Located at the central portion of the Walnut Creek Watershed, the NSNWR was established in 1990 to reconstruct native tall-grass prairie on the landscape (Schilling and Spooner 2006), with new prairie seedings added each year. Portions of the NSNWR awaiting restoration are either leased to farmers in the area for crop production or maintained in perennial cover.…”
Section: Methodsmentioning
confidence: 99%